THE IMPACT OF INFORMATION TRANSPARENCY ON FIRM PERFORMANCE: EVIDENCE FROM CHINA - Fang, Yangming (PEOPLE: International Journal of Social Sciences, 2024)
Nowadays, with the concern of the public for corporate social responsibility, firms are increasingly concerned with social responsibility, and they need to know whether social responsibility is favourable for their profit. The study focuses on 3,536 Chinese firms and collects the data of them from 2006 to 2021. The study analyses the data with the method of regression to find the relationship between information transparency and ROA, as well as the moderating effects of voluntary disclosure and company loss. We also run regressions with a lagged score of information transparency instead of the current score as a robust check. After analysis, we find that a high level of information transparency is significantly beneficial for a great firm performance. Additionally, this relationship exhibits an increasing marginal effect in the firms in which information disclosure is voluntary and the firms that are facing losses. The findings of this study provide useful guidance for firm managers about whether to develop high information transparency